2012
DOI: 10.1166/jnn.2012.5199
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer Nanocomposite Films Reinforced with Nanocellulose Whiskers

Abstract: A xylan nanocomposite film with improved strength and barrier properties was prepared by a solution casting using nanocellulose whiskers as a reinforcing agent. The 13 C cross-polarization magic angle spinning (CP/MAS) nuclear magnetic resonance (NMR) analysis of the spectral data obtained for the NCW/xylan nanocomposite films indicated the signal intensity originating from xylan-cellulose interactions. Qualitatively, the spectral data obtained for the NCW/xylan nanocomposite films indicated that the amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…However, in that study, the OsAX used was from a different supplier. The crystallinity of 26% was also obtained by Saxena et al (2011) who studied OsAX films plasticized with 100% sorbitol (of the weight of the OsAX). In the present study the average size of single xylan crystallites in OsAX films was determined to be 5 to 10 nm.…”
Section: Crystallinitymentioning
confidence: 89%
“…However, in that study, the OsAX used was from a different supplier. The crystallinity of 26% was also obtained by Saxena et al (2011) who studied OsAX films plasticized with 100% sorbitol (of the weight of the OsAX). In the present study the average size of single xylan crystallites in OsAX films was determined to be 5 to 10 nm.…”
Section: Crystallinitymentioning
confidence: 89%
“…Since NMR relaxation times are sensitive to molecular dynamics, there have been previous studies of water-lignocellulose systems as well as of water–polymer interactions in hydrogel polymers, , with 1 H NMR as the main experimental method. While valuable conclusions are drawn both about microscopic and macroscopic features, only a few issues are definitely settled. A limitation of 1 H NMR as a molecular tool for water–polymer interaction studies is its poor ability to permit quantitative interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Saxena and colleagues [ 105 ] prepared xylan/sorbitol composite film with good strength and barrier properties by using nanocellulose whisker (NCW) as the reinforcing agent. It was found that the X-ray diffraction peaks of xylan-NCW nanocomposite films changed from weak and broad peaks to sharp peaks with the increase in NCW content.…”
Section: Hemicellulose-based Nanocomposite Filmmentioning
confidence: 99%